Pelvic Congestion Syndrome in a Post-Cesarean Section and Postpartum Patient: A Case Report - Pupu Ayu Wandira Otgina Mansyah; I Nyoman Harriyasa Sanjaya; Gusti Ngurah Agung Eka Wiguna (Lembaga Pengembangan Kinerja Dosen, 2026)
Pelvic Congestion Syndrome (PCS) is a recognized cause of chronic pelvic pain resulting from impaired venous drainage and is most commonly observed in multiparous women. Pregnancy, hormonal changes, and cesarean delivery are known risk factors for this condition. This study was designed as a descriptive case study to illustrate the clinical identification and multidisciplinary management of PCS in a postpartum patient following cesarean section. We report the case of a 38-year-old woman (P3A0) who presented 24 hours after cesarean section with abdominal bloating and leg swelling. Physical examination revealed a well-healed surgical incision, a uterine fundal height two fingerbreadths above the symphysis pubis, mild lower-limb edema, and pelvic tenderness. Pelvic ultrasonography demonstrated dilated and tortuous adnexal veins, more prominent on the left side, findings consistent with PCS. Multidisciplinary management involving obstetrics, internal medicine, and radiology played a crucial role in establishing an accurate diagnosis and initiating effective treatment. Early recognition and coordinated care were essential in preventing progression to chronic pelvic complications. This case highlights the importance of considering PCS in postpartum women presenting with unexplained pelvic pain or edema, as timely diagnosis and appropriate management can improve outcomes and reduce long-term morbidity.